"The More We Know, the More We're Able to Help": Participatory Development of an Evaluation Framework for Community Health Worker Programs. Issue 5 (21st September 2022) - Sherman, Mya; Covert, Hannah H.; Lichtveld, Maureen Y.
Abstract : Context: It is critical to evaluate community health worker (CHW) programs to maximize effectiveness. However, there is little consensus, and structure, for how to evaluate such programs. Objective: The purpose of this study was to develop a flexible framework for evaluating components of CHW programs in community and clinical settings. Design: Semistructured interviews were conducted with CHWs and their supervisors to determine evaluation categories for the framework. A survey was then administered to pilot the framework at federally qualified health centers and community-based organizations with existing CHW programs. Setting: Eighteen federally qualified health centers and community-based organizations in Louisiana, Mississippi, Alabama, and Florida. Participants: Participants consisted of 23 CHWs and 19 CHW supervisors. Results: Interview participants directly informed the development of an evaluation framework for CHW programs. The framework consists of 7 evaluation categories: client relations, intraorganizational relations, interorganizational relations, capacity development, program effectiveness, cost-efficiency, and sustainability. Survey respondents specified best practices for program implementation for each evaluation category. Recommendations for CHW program evaluation include tailoring evaluation efforts and data collection methods to program context, using mixed-methods approaches for collecting evaluation data, and streamlining evaluation efforts with an organization's existing evaluation systems. Conclusions: The evaluation framework is a flexible and practical model for collecting information needed for monitoring and evaluating CHW programs. By relying on practitioners' perspectives, this study contributes to an evidence base for implementing and evaluating CHW programs.